Pengembangan Tes IPA Dua Tingkat Berbasis Permainan Jumanji Untuk Mengukur Pemahaman Konsep - Tutik Yuliatun; Kristina Uskenat; Selestina Kostaria Jua (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
This study aims to develop a two-level Natural Science (IPA) test instrument based on the jumanji game in measuring understanding of the concept of work and simple planes. The research method in this case is a quantitative method with a modification of the development model. The measurement instrument developed in this study is a two-level science test or a reasoned multiple choice test specifically for the business chapter and simple planes. This research instrument that has been developed was tested on 256 students of SMP Abu Bakar. The results of this study indicate that a measurement instrument has been produced in the form of a two-level science test based on the jumanji game which can measure students' understanding of concepts about business and simple and reliable machines that are valid and reliable. These results are evidenced by the validity and reliability of the two-level science test, which are 0.83 and 0.53 respectively. Meanwhile, the achievement of students' understanding of concepts related to business and simple machines is 51% which is in the high category. The students' conceptual understanding measured using the two-level science test is high because it exceeds the minimum criteria that have been determined.